Under the aegis of science the Philippine scientific community before the second world war - Baldoza, Jonathan Victor (Philippine studies : historical and ethnographic viewpoints)
"This article explores the formation of a prewar community of Filipino scientists nurtured and trained within the scientific order that American scientists installed, developed, and managed in the early part of the twentieth century. It examines vital institutions that shaped and recast the landscape of scientific knowledge production in the Philippines before the Second World War. It explores the ways by which Filipino scientists, endowed with intellectual legitimacy but ambiguously situated in relation to US rule, actively participated in planning for the forthcoming nation, bearing the torch of science as key to the nation's progress and modernity."